Emergence of an NDM-5-producing clinical Escherichia coli isolate in Egypt. (July 2016) - Soliman, Ahmed M.; Khalifa, Hazim O.; Ahmed, Ashraf M.; Shimamoto, Toshi; Shimamoto, Tadashi
Highlights: The first occurrence of New Delhi metallo-β-lactamase 5 (NDM-5), carried on an IncI1-Iγ-type plasmid in a multidrug-resistant clinical Escherichia coli strain in Egypt, is reported. This E. coli was found to belong to sequence type (ST) 5018 and to carry other resistance genes including bla CTX-M-15, bla CMY-42, bla OXA-1, and aac(6′)-Ib-cr and class 1 integron with two gene cassettes ( dfrA17–aadA5 ). Southern blot hybridization showed that bla NDM-5 was located on a plasmid of >93 kb in size. Summary: The first occurrence of New Delhi metallo-β-lactamase 5 (NDM-5), carried on an IncI1-Iγ-type plasmid of >93 kb in a multidrug-resistant Escherichia coli strain in Kafr El-Sheikh, Egypt, is reported. The strain was isolated from a wound pus swab from a patient diagnosed with a fracture of the right femur. This E. coli strain was found to belong to sequence type (ST) 5018 and also to carry other resistance genes, including bla CTX-M-15, bla CMY-42, bla OXA-1, and aac(6′)-Ib-cr .